"Risk Watch": Cluster randomised controlled trial evaluating an injury prevention program. Issue 2 (19th April 2007) - Kendrick, Denise; Groom, Lindsay; Stewart, Jane; Watson, Michael; Mulvaney, Caroline; Casterton, Rebecca
Abstract : Objective: to evaluate the effectiveness of a school-based injury prevention program. Design: Cluster randomised controlled trial. Setting: 20 primary schools in Nottingham, UK. Participants: 459 children aged 7 to 10 years. Intervention: The "Risk Watch" program delivered by teachers, aimed at improving bike and pedestrian, falls, poisoning and fire and burns safety. Main outcome measures: Safety knowledge, observed safety skills and self-reported safety behaviour. Results: At follow-up, intervention group children correctly answered more fire and burn prevention knowledge questions than control group children (difference between means 7.0% (95% CI 1.5% to12.6%)). Children in intervention group schools were more likely to know the correct actions to take if clothes catch fire and the correct way to wear a cycle helmet (difference between school means 35.3% (95% CI 22.7% to 47.9%) and 6.3% (95% CI 1.4% to 11.1%) respectively). They were also more likely to know the correct actions to take in a house fire and on finding tablets (OR 2.80 (95% CI 1.08 to 7.22) and OR 3.50 (95% CI 1.18 to 10.38) respectively) and correctly demonstrated more safety skills than control group children (difference between means 11.9% (95% CI 1.4% to 22.5%)). There was little evidence to suggest the first year of the program impacted on self-reported safety behaviours. Conclusions: The Risk Watch program delivered by teachers in primary schools increased some aspects of children's safety knowledge and skills and primary schools should consider delivering this program. Longer term, larger scale evaluations are required to examine retention of knowledge and skills and impact on safety behaviours and child injury rates.